The Impact of Divine Healing on Evangelism Based on Acts of the Apostles Chapter 3 and Its Significance for Believers - Hermina Hermina (Theological Journal Kerugma, 2023)
Divine healing sometimes sparks fervent debates among Bible-believing individuals about its central role in the Bible. The undeniable fact is that divine healing occurred in both the Old and New Testaments, indicating that it is not in conflict with the teachings of the Bible. When Jesus healed someone, as He frequently did, His motive was never self-glorification but rather to aid those in need. He is a compassionate Healer, a Savior, addressing both physical and spiritual ailments. In Acts of the Apostles, Chapter 3, a divine healing event is recounted, and it holds significance for evangelism. To ensure accurate and accountable data in this study, the author employed library research and exposition studies using inductive methods. The primary goals of this study were, first, to provide a clear and detailed explanation of divine healing based on Acts Chapter 3. Second, to elucidate the close relationship between faith and divine healing. Lastly, to explore the impact of divine healing on evangelism as reflected by its followers. In conclusion, divine healing is a manifestation of God's work for those who have faith in the name of Jesus. It serves the purpose of bringing individuals closer to God, nurturing love for God, inspiring a life dedicated to glorifying Him, and producing positive impacts on others.